Recrudescence des mouvements insurrectionnels a dominance tutsi en RDC Expression de la conquête de l’espace territorial, militaire ou politique ? - Bolelame, Emile Libonze; Basunga, André Basoy (IJRDO - Journal of Social Science and Humanities Research, 2018)
Since 1997 Democratic Republic of Congo has kept recording (undergoing) insurrectionary recurrent movements (AFDL in 1997, RDC in 1998, CNDP in 2004, M23 in 2012) dominated by the Tutsi ethnic minority (from Rwanda) of Rwandan origin in the North and South Kivu. To conquer territorial, military and political Congolese space this ethnic minority operates (uses) by means of three strategies namely craftiness (cunning), negotiations and violence (recourse to violence).This study focuses on the fragility of the Congolese State, conflicts and inters ethnics violences, land and food pastoral question, sociopolitical factors, geostrategic issue as major causes of fresh up surge of insurrectionary movements in both Kivu. These conquest strategies proved to be efficient because they have let the Tutsi minority, as compared to other minor tribes, to hold military and political positions and exploit vast land spaces to the detriment of native communities of Kivu, which think themselves deprived of their lands.